PERFORMANCE OF THE CLONE Eucalyptus urograndis IN A CONVENTIONAL AND SILVOPASTORAL SYSTEM - de Farias, Jorge Antonio; de Campos de Jesus, Luana; Pasa, Débora Luana; Souza, Sara Chagas de (Floresta, 2022)
The objective of this study was to analyze forest productivity, comparing the financial viability of a silvopastoral system versus a conventional forest plantation, both using the clone of the hybrid of Eucalyptus urograndis. For the survey of the volume data, nineteen plots of 40.0 x 15.0 m (600 m²) were installed in conventional planting and fifteen plots of 25.0 x 32.0 m (800 m²) in silvopastoral planting. All tree diameters and heights of each plot were measured. The hypsometric relationship models were obtained using the Stepwise method and the trees were cubed using the Smalian method. The volumes were separated into assortments, according to the sales options for the local market. The financial analysis considered cash flows from the year of implementation until the cutting age (7 years), considering the costs spent for the formation and maintenance of the forest throughout the cycle, discounted at an interest rate of 6.75% per year and the volume sold at market value, considering standing wood, at the end of the cycle. The following were evaluated: net present value, equivalent annual value, internal rate of return, expected value of land and average cost of production. The two production systems were considered economically viable for the suggested 7-year rotation, however the silvopastoral system showed results that demonstrate greater financial viability caused mainly by the lower cost of implementation and maintenance, and to the greater volume of the assortments with greater added value (S1 and S2).